Dari Visi Menuju Visitasi: Orkestrasi Kepemimpinan Transformasional Kepala Sekolah dalam Persiapan Akreditasi - Ainul Yakin; Misbahul Arifin (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study explores the orchestration of transformational leadership by school principals in integrating leadership vision with daily operational practices to support school accreditation preparation, focusing on the implementation of Bass's four components of transformational leadership and the transformation of school culture towards continuous learning. Using a qualitative case study approach at SMP Lubbul Labib, Probolinggo, East Java, data were collected through in-depth interviews with 7 informants, 3-month participant observation, and document studies, then analyzed using the Miles and Huberman model with member checking validation. The findings reveal that the principal successfully integrated transformational leadership vision into operational practices through a systematic approach, where the implementation of four transformational leadership components (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration) proved effective in transforming school culture from conventional to continuous learning culture that positions accreditation as a development opportunity rather than an administrative burden. Theoretically, this study strengthens the argument that transformational leadership is a multidimensional construct requiring contextual implementation in educational organizations, while practically introducing the concept of "transformational leadership orchestration" that provides concrete mechanisms to bridge the gap between leadership vision and operational practices, positioning accreditation as a catalyst for sustainable organizational development.